(untitled) (Web of Teachers: Inderscience Research, 2024)
"In the second half of the 19th century and the beginning of the 20th century, Russian artists came here, even worked here all the time, and reflected the life and nature of the people of Turkestan from a high humanistic position." They talk about artists and sculptors who came to Russia.